Positional synchronization and performance in football teams - Gomes, José Manuel Marques (2018)
Positional data is collected using automatic tracking systems and have been used to understand how the location of each player varies in the pitch throughout a football match. These data can be used to assess players’ movement synchronization. The aim of this study was to identify the relation between movement synchronization and match statistics, so as to investigate the behavior of positional synchronization towards the match according to opponent level. The sample included 12 matches from a professional football team (season 2016/2017). Positional data was retrieved using 20Hz TRACAB System and processed in MATLAB® (The MathWorks Inc., Natick, MA, USA). Players’ movement synchronization was quantified by calculating the relative phase of all dyads of outfield teammates during the entire match and for a time window of 1-min and 5-min, for both displacement axes. Notational analysis was carried using LongoMatch – Sports Video Analysis Software. Correlation analysis was used to test the relationship between positional synchronization variables and notational variables. The intra-team synchronization data were considered as dependent variables and compared according to the levels of opposition (stronger and weaker opponents). One-way ANOVA was used to compare notational variables and the percentage of time of dyadic synchronization according to opposition level. Univariate ANCOVA analyzed the relationship between positional synchronization values and notational variables, using opponent level as co-variable. Opponent level applied differences in positional synchronization. Pass efficacy (%) was negatively related to longitudinal and latitudinal synchronization. The number of accurate passes were highly related to players’ synchronization. Latitudinal synchronization showed to be highly positively related to the number of wrong passes. Higher values of accurate passes and consequently pass efficacy were observed when the team registered similar levels of latitudinal and longitudinal synchronization. A higher number of wrong passes were observed when latitudinal synchronization presented higher values and longitudinal synchronization lower values. Pass efficacy (%) showed differences according to the synchronization groups, but not according to the opponent level. These findings suggest that players must move synchronized towards the goal and vary their movement in a parallel axis to the goal, in order to increase the odds of successfully passing the ball to their teammates